Malaria and Maternal Mortality In Gezira-Sudan - Mohamed EL Sanousi, Mohamed EL Sanousi; AL Hassan, Abdul Rahman Abdul Hafeez; Ahmed Abd EL Salam, Muawia Mohamed; Mirghni, Omer Ahmed (Gezira Journal of Health Sciences, 2007)
The objectives of this study include:(1) to identify the magnitude of malaria as a cause of maternal mortality (MM) (2) to study the demographic characteristics of MM cases caused by malaria and (3) to identify the actual cause of MM due to malaria. Methods : This is a six years hospital based retrospective review of hospital records of ladies died due to malaria in Wad Medani Teaching Hospital for Obstetrics and Gynaecology (WMTHOG), form1 January 1998 to 31 December 2003. Results : malaria caused 10% to 40% of MM per year. The mean age was 27.57 years, most of them were primigravidae and from rural areas. 37.8% of the deaths occurred between 28 and 36 weak of gestation. The median duration of stay in hospital was two days. However 32.4% of deaths stayed for less than 24 hours that indicated severe and serious clinical presentations. The main causes of death due to malaria or its complication were: anaemia (24.3), cerebral malaria (21.6%), circulatory failure (12.51 ) and renal failure (8.1%). Others were pulmonary oedema , hyperpyrexia  , puerperal psychosis , abortion , severe epistaxis , cardiac  arrest , black water fever, electrolyte imbalance, and hepatic failure. The study recommended effective prevention of malaria and an intensive care approach in its management.